Analyzing and Reporting of BIT Students' Performance Using Business Intellingence (BI) Tool - Norhayati, Ahmad (2005)
Specifically, this research of study analyzes the students’ academic performance, which focuses on the sample of students who enrolled in Bachelor of Information Technology (BIT) program at Universiti Utara Malaysia (UUM). The current BIT students as well as the graduated BIT students have been analyzed to determine the students’ performance, whether it is influenced by their educational background or other factors. The Business Intelligence (BI) tool has been proposed into the current system at Faculty of Information Technology (FTM). This new system is to generate statistical and multidimensional analysis as well as to produce the report such as to determine the students’ overall performance for academic decision making process. Findings indicated that the BIT students overall performance were not really influenced by their educational background. However it has been found out that there are several other factors that could affect their performance such as the choice of the program IT (whether first choice or not), the difficulty of the subjects, the level of students’ interest and commitment, the percentage of class attendance and also the students’ satisfaction towards facilities, services and environment at UUM.